Latin America: A Model for the Global Plant Cryopreservation Initiative - Ellis, David; Vollmer, R.; Souza, F.V.D.; Azevedo, V.C.R. (2025)
Latin America (Mexico, the Caribbean, and Central and South America) is a megadiverse region. From Mexico and the Caribbean, through Central America to the Amazon and Andes, Latin America’s botanical diversity contributes significantly to global food production and security, as it is the region of domestication for crops essential to human survival, including maize, potato, cassava, sweet potato, and beans. However, Latin America is also one of the most threatened regions with massive loss of native habitat where cultivars of these domesticated crops and their wild relatives, invaluable for new traits important for the adaptation to the abiotic and biotic challenges from climate change, currently exist. Many of these crops are vegetatively propagated, and their unique allelic makeup is crucial to conserve. Unfortunately, these unique genotypes cannot be conserved as seed and are at risk of vanishing forever due to the lack of secure conservation methods. The Global Plant Cryopreservation Initiative (GPCI) is addressing this challenge by providing a secure, long-term method for conserving plant diversity which cannot be conserved as botanical seed. The Latin America hub for the GPCI, at the International Potato Center (CIP) in Peru, is a model for how to mobilize and build capacity at the country level through national programs to conserve their genetic resources. Starting with a regional in-person workshop in 2022, CIP has maintained momentum for a plant cryopreservation network in Latin America by holding annual regional virtual cryopreservation meetings. CIP provided in-person capacity training for Latin American researchers in plant genetic resources conservation, with a special focus on cryopreservation. CIP has also implemented national plant cryopreservation programs in Ecuador and Chile, which include backing up their accessions in CIP’s “cryo-vault.” These activities provide the foundation for the future of a strong, lasting plant cryopreservation community of practice throughout Latin America.